Impact of Obstetric Emergency High-Fidelity Simulation on Maternity Nurses' Self-Efficacy in the Rural Hospital Setting. Issue 3 (May 2021) - Ehmke, Sabrina; Swan, Marilyn; Van Gelderen, Stacey; Bourdeanu, Laura
Abstract: Purpose: The purpose of this study was to explore the impact of an obstetric emergency high-fidelity simulation on maternity nurses' perceived self-efficacy levels at three different time points. Study Design: We used a quasi-experimental, repeated measures design. Methods: A convenience sample of maternity nurses recruited from three institutions within a single rural health care system participated in simulation exercises at an academic high-fidelity simulation center. They completed the Obstetric Nursing Self Efficacy survey before, immediately after, and 2 months following the simulation. Results: Twenty-nine nurses were included in the analysis. All were women and Caucasian. Most (72.4%) had a baccalaureate nursing degree, with an average nursing experience of 11 years (range 1 to 44 years), and <5 years of OB experience (55.1%). Self-efficacy scores were 55.62 ( SD = 9.8), 58.93 ( SD = 8.9), and 61.86 ( SD = 9.5) for pre-, post-, and 2 months postsimulation, respectively. There were significant changes from self-efficacy scores before the simulation when compared with scores 2 months after the simulation ( p < 0.001), with a medium effect size of .45. Clinical Implications: High-fidelity simulation can improve maternity nurses' perceived self-efficacy in managing emergency obstetric clinical situations. Health care institutions should consider investing in high-fidelity simulation education or partnering with academic institutions that have simulation centers to promote maternity nurses' self-efficacy that can potentially translate into improved clinical skills and improved patient outcomes. Abstract : High-fidelity simulation of obstetric emergencies may be helpful for maternity nurses practicing in rural hospital settings to improve their self-efficacy, knowledge, and skills. In this project, nurses at a small regional health system with three rural hospitals partnered with nurses in an academic institution that has a simulation center to offer obstetric emergencies education for maternity nurses.